The micropolitics of choice in Italy: How the law affects lesbian and bisexual women's daily life. Issue 3 (3rd July 2019) - Gusmano, Beatrice; Motterle, Tatiana
Abstract: This article stems from three years of fieldwork (2015–2017) in the context of a five-year-long, European-Research-Council-funded research project called INTIMATE—Citizenship, Care and Choice: The Micropolitics of Intimacy in Southern Europe, a comparative qualitative study that involves three countries (Italy, Portugal, and Spain) and studies intimate citizenship and the micropolitics of daily life of LGBTQ people. The article focuses specifically on the Italian case and shows how non-heterosexual women deal with the scarce legislative protection Italy grants. Our aim is to reflect upon the reciprocal influence of different axes from public and private spaces and on how they impact the micropolitics and the daily choices of our lesbian, bisexual, and pansexual participants. More specifically, considering the lack of legal and social recognition of lesbian experiences in Italy, we will focus on the different strategies of reaction, assimilation, and resistance employed by participants in their private and public life. The three-year-long fieldwork covered the period between the proposal of the bill on same-sex civil unions and the first year after Act 76/2016 came into force. This allows us to sketch a brief diachronic analysis of its functioning, in particular from the perspective of the very subjects it impacts.